Ocular involvement in beta thalassemia major: a prospective study in an Indian cohort - Kumble, Dhanalakshmi; Sekhon, Prabhjot Kaur; C., Gayathri Devi (International Journal of Contemporary Pediatrics, 2017)
Background: Thalassemia is the commonest haemoglobinopathies worldwide. Repeated blood transfusions lead to hemosiderosis which affects all the organs in the body including eyes. This study aims to study Ocular manifestations in these children and its correlation with age and serum Ferritin level. Methods: 75 children diagnosed with B-Thalassemia major (BTM) and on regular transfusions underwent detailed Ocular examination between 2013 and 2015, including visual acuity, slit lamp bio microscopy, direct & indirect Opthalmoscopy). Results: Mean age for children was 9.73 years, with 77 % males and 23% females. Average S. Ferritin being 2701.96 ng/dl. The most common eye changes seen were in the Retina (32%, n=24), Iris (34.7%, n=26) and lens (32%, n=24). Retinal changes were temporal Retinal thinning (29.3%, n=22), retinal venous engorgement (21.3%, n=16), vessel tortuosity (17.3%, n=13), atrophy of disc (17.3%, n=13). Lens opacities were seen in 32 %, posterior sub capsular haze, streaks in posterior capsule, and heterochromia in 34.7%. Retinal changes correlated with duration of disease in children above 10 years and with increasing Serum Ferritin levels. Conclusions: Corneal dryness, lenticular opacities, disc atrophy and thinning were observed in children with B- Thalassemia and on blood transfusions. These changes increased with duration of disease. Hence there is need to screen BTM adolescents and follow up.